Mechanical properties of green recycled polypropylene composites: effect of maleic anhydride grafted polypropylene (MAPP) coupling agent - Zulkifli, Nur Izzati; Samat, Noorasikin (Trans Tech Publications, Switzerland, 2013)
Recycled polypropylene/microcrystalline cellulose (rPP/MCC) composites were prepared by adding different loadings of maleic anhydride grafted polypropylene (MAPP) coupling agent. The tensile, impact and morphological properties of the composites were investigated. The obtained results show that the tensile and impact strengths of the composites were significantly enhanced with the addition of MAPP loading from 2 to 5 wt%, as compared with unfilled rPP/MCC composites. However, it was found that at low filler content, different amounts of MAPP resulted in no appreciable change in the tensile strength and modulus. Moreover, dynamic mechanical analysis (DMA) results indicated that, increasing the amount of MAPP loading from 2 to 5 wt% in rPP/MCC provide better stiffness of the composite compared to those neat rPP and neat PP. Field emission scanning microscopy (FESEM) has shown that the composite, with MAPP loading, promotes better fiber–matrix interaction.